Bioprospecting of Adhatoda vasica for Identification of Novel Compounds using Chromatographic Methods and Screening for Anti-diabetic and Antioxidant Activity - Patil, Akshay Milind; Janvale, Ganesh Bapurao; Bhusari, Dhanvarsha Pralhad; Shinde, Shrutkirti Shahaji (Journal for Research in Applied Sciences and Biotechnology, 2023)
This investigation column eluted fractions of leaf Adhatoda vasica of was assessed for its phytochemical screening, column chromatography, thin layer chromatographic studies, protease activity, anti-inflammatory activity, antidiabetic activity and antioxidant activity. Phytochemical screening reflects the presence of alkaloid, flavonoids, coumarins, terpenoids, steroids, emodin’s, Quinone’s. Column chromatography method was used for purification of bioactive compounds. Thin layer chromatographic study was carried out by using various solvent system of different type of polarity of n- butanol, acetic acid and acetone. TLC profiling shows pure band at 254nm and 366 nm. The strong “proteolytic activity” also pointed out in purified fraction of eluted fraction. In vitro anti-inflammatory activity was evaluated using albumin denaturation fraction 3, showing highest activity 75% followed by fraction 5 (62.73%), membrane stabilization assay fraction 6 (80.23%) followed by fraction 3 (64.65%) and proteinase inhibitory activity of fraction 5(88%) followed by fraction 7 (87.68%) at concentration 500 µg/ml. Aspirin (90.87%) was used as standard drug for the study of anti-inflammatory activity. In vitro antidiabetic activity was performed using Alfa amylase inhibition assay. Highest activity was showed in fraction 4 (79.05 %) and fraction 5 (77.05 %) at concentration 500 µg/ml. Antioxidant activity was performed by reducing power assay fraction number 2 has higher absorbance 1.04 at 500µg/ml followed by reducing power of column eluted fraction was compared with ascorbic acid as standard showing higher absorbance 0.93 at 500µg/ml.